1993
DOI: 10.2105/ajph.83.7.979
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion counseling of chronic-disease patients during primary care visits.

Abstract: OBJECTIVES. This study was designed to provide an empirical description, based on a review of visit audiotapes, of primary care practice with chronic-disease patients. METHODS. We analyzed 439 interactions between adult patients with chronic disease and 49 physicians. We explored the content, frequency, intensity, and dynamics of health promotion discussion during these routine visits. RESULTS. There was evidence of health promotion discussion in more than half (53%) of the audiotapes reviewed. When life-style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…In another study, audiotapes of patient visits for chronic diseases showed that 53% of the visits included prevention activities that required about 4.5 minutes per encounter. 40 Rafferty studied service delivery in primary care clinics for indigent patients and found that clinicians spent 11% of their time on prevention (about 7 minutes per patient per year). Half of this time was spent screening for breast and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, audiotapes of patient visits for chronic diseases showed that 53% of the visits included prevention activities that required about 4.5 minutes per encounter. 40 Rafferty studied service delivery in primary care clinics for indigent patients and found that clinicians spent 11% of their time on prevention (about 7 minutes per patient per year). Half of this time was spent screening for breast and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys in other countries over the past two decades have had similarly disappointing results with only a minority of patients reporting having been advised or even asked about alcohol use (Table S1; see supporting information details at the end). Further, alcohol-related discussions that do occur last a few minutes or less [5][6][7].…”
mentioning
confidence: 99%
“…Physicians are in a good position to provide screening and counseling, as most adults visit a physician at least once per year 5 . However, screening and counseling rates are low, 6,7 and commonly used counseling strategies may be inadequate to effect behavioral change 8,9 …”
mentioning
confidence: 99%